Chocolate in Mesoamerica : A Cultural History of Cacao - McNeil, Cameron L. (Book collections on Project MUSE., 2006)
From the botanical structure and chemical makeup of Theobroma cacao and methods of identifying it in the archaeological record, to the importance of cacao during the Classic period in Mesoamerica, to the impact of European arrival on the production and use of cacao, to contemporary uses in the Americas, this volume provides a richly informed account of the history and cultural significance of chocolate.